Age differences in online news consumption and political expression in the United States, United Kingdom, and France - Boulianne, Shelley; Shehata, Adam (My University, 2021)
Younger and older generations are differently motivated in relation to news consumption and online political expression. In this paper, we suggest that different modes of citizenship characterize younger and older generations. To test the differential role of political interest in news consumption and online political expression, we use a survey of 3,210 people from the United States, 3,043 from the United Kingdom, and 3,031 from France. Our findings suggest that young citizens are more frequent users of online news overall and that the rank order of different news activities replicates cross-nationally. The frequency of online political expression is negatively related to age, with older people less likely to post online. Age moderates the relationship between political interest and news consumption as well as news consumption and online political expression. The correlations of these sets of variables are stronger for younger respondents compared to older respondents. These findings hold across the three countries under study. We explain these patterns in terms of changing citizenship norms and discuss the implications for democracy.
Keywords: youth; online news; political expression; cross-national